2019
DOI: 10.1007/jhep01(2019)138
|View full text |Cite
|
Sign up to set email alerts
|

One-loop contribution to dark-matter-nucleon scattering in the pseudo-scalar dark matter model

Abstract: Recent dark matter (DM) direct searches place very stringent constraints on the possible DM candidates proposed in extensions of the Standard Model. There are however models where these constraints are avoided. One of the simplest and most striking examples comes from a straightforward Higgs portal pseudoscalar DM model featured with a softly broken U (1) symmetry. In this model the tree-level DM-nucleon scattering cross section vanishes in the limit of zero momentum-transfer. It has also been argued that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 28 publications
(48 reference statements)
2
74
0
Order By: Relevance
“…We computed the pNG DM-nucleon cross section at one-loop level for all of our samples after utilising the results of ref. [27]. We found that none of the points in our scan are challenged by current direct detection limits from XENON1T (2018).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…We computed the pNG DM-nucleon cross section at one-loop level for all of our samples after utilising the results of ref. [27]. We found that none of the points in our scan are challenged by current direct detection limits from XENON1T (2018).…”
Section: Discussionmentioning
confidence: 57%
“…1 Thus, a pNG DM model offers a natural way of evading the strong direct detection limits. A leading-order contribution to the pNG DM-nucleon cross section in the zero-momentum limit appears at the one-loop level [27,28]. For typical DM velocities in our galaxy, v χ ∼ 10 −3 , it can easily dominate over the tree-level contribution.…”
mentioning
confidence: 81%
See 3 more Smart Citations